Exploring the residential segregation of Chinese languages and language groups of the Indian subcontinent in Sydney. (26th May 2021) - Johnston, Ron; Forrest, James; Siciliano, Frank
Abstract: Most studies of the spatial integration of immigrant groups and their descendants in multicultural cities use broad categories only, such as ethnic/racial identity and birthplace/ancestry, implicitly assuming that such groups are homogeneous. Some are not. Instead, they are subdivided according to further cultural characteristics such as language and religion, which may be central to group identity and residential location choices. Using data from the 2016 Australian census, we examine the spatial distribution of 17 language groups with 1, 000 or more persons in Sydney—five Chinese languages and 12 from the Indian subcontinent—at five spatial scales: major regions, regions, districts, suburbs, and neighbourhoods. We find consistent evidence of significant levels of segregation among those speaking the 17 languages at the neighbourhood level, but a lack of differentiation among other scales in Sydney.